Indenture as a self-enforced contract device: an experimental test - Alexander S. Kritikos; Jonathan H. W. Tan (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We experimentally test the efficacy of indenture as a self-enforced contract device. In an indenture game, the principal signals the intention of payment-on-delivery, by tearing a banknote and giving the agent half of it as prepayment; the agent receives the completing half after delivering the service. By forward induction, cooperation is incentive-compatibly self-enforcing. The indenture performs very well, inducing a significantly higher level of cooperation than that in a three-stage centipede game, which we use to benchmark the natural rate of cooperation. The difference between cooperation rates in both games increases over time.
Keywords: C91; D64; J41; 330; Cooperation; experiment; contracts; indenture; reciprocity; Vertrag; Agency Theory; Reziprozität; Spieltheorie; Test; Arbeitsvertrag; Theorie